Effects of perioperative enteral glutamine on surgical outcome in gastrointestinal cancer patients - ., Raghavendra; S., Raghupathi (International Surgery Journal, 2019)
Background: Previous trials have shown that perioperative glutamine could protect patients from infectious complications after gastrointestinal cancer operations. Methods: 54 patients with a planned elective operation for gastrointestinal cancer were divided into two groups: GROUP A: patients given glutamine enriched enteral nutrition perioperatively (n=27), GROUP B: patients given enteral feed without glutamine (n=27). Patients were assessed in terms of post-operative complications like infective complications, anastomotic leak, need for reintervention, length of hospital stay and mortality. Results: In group A seven patients and in group B six patients had surgical site infection post operatively (p=0.750). In group A five patients and in group B three patients had lung and urinary tract infection post operatively (p=0.444). In group A three patients and in group B five patients had intra-abdominal abscess/collection post operatively (p=0.444). In group A one patient and in group B three patients had anastomotic leak post operatively (p=0.299). In group A three patients and in group B three patients had reintervention in form of ultrasound guided aspiration and ultrasound guided pigtail aspiration for intra-abdominal collection (p=1.000). In group A and in group B mean length of hospital stay was 26 days and 23 days respectively (p=0.346). In group A and in group B mean length of post-operative hospital stay was 13 and 12 days respectively (p=0.642). There was no mortality in our study. No significant difference between the groups was found in complication rates, length of hospital stay. Conclusions: Routine perioperative glutamine to the patients undergoing major gastrointestinal surgery is not beneficial.